2019
DOI: 10.1002/1878-0261.12588
|View full text |Cite
|
Sign up to set email alerts
|

miR‐15a‐5p, miR‐15b‐5p, and miR‐16‐5p inhibit tumor progression by directly targeting MYCN in neuroblastoma

Abstract: Neuroblastoma (NB) is the most common extracranial solid malignancy in children. Despite current aggressive treatment regimens, the prognosis for high‐risk NB patients remains poor, with the survival of less than 40%. Amplification/stabilization of MYCN oncogene, in NB is associated with a high risk of recurrence. Thus, there is an urgent need for novel therapeutics. The deregulated expression of microRNA (miR) is reported in NB; nonetheless, its effect on MYCN regulation is poorly understood. First, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 70 publications
1
79
0
Order By: Relevance
“…3e, f). Ago2, an important component of RNA induced silencing complex (RISC), generally interacts with RNAs [31,32]. Then a RIP binding assay was conducted by using anti-Ago2 antibody in 293 T cell line, the results showed that the level of HOST2 and let-7b/miR-1266 was higher in anti-Ago2 group than that in anti-normal IgG group (Fig.…”
Section: Host2 Acted As a Sponge Of Let-7b And Mir-1266 In Tnbc Cellsmentioning
confidence: 98%
“…3e, f). Ago2, an important component of RNA induced silencing complex (RISC), generally interacts with RNAs [31,32]. Then a RIP binding assay was conducted by using anti-Ago2 antibody in 293 T cell line, the results showed that the level of HOST2 and let-7b/miR-1266 was higher in anti-Ago2 group than that in anti-normal IgG group (Fig.…”
Section: Host2 Acted As a Sponge Of Let-7b And Mir-1266 In Tnbc Cellsmentioning
confidence: 98%
“…For example, lncRNA CR749391 was reported to promote the progression of gastric cancer by sponging miR-181a ( 28 ); lncRNA HCG18 promotes the development of NPC by functioning as a ceRNA of miR-16 to upregulate G1/S-specific cyclin-D1 expression levels ( 29 ) and lncRNA AFAP1-AS1 was observed to function as a ceRNA of miR-423-5p to promote NPC metastasis by activating the Rho/Rac signaling pathway ( 30 ). Previous studies have also indicated that miR-16 is associated with cancer regulation, including cervical cancer, bladder cancer and neuroblastoma ( 31 33 ). Consistent with these findings, the present study also observed an interaction between KIF9-AS1 and miR-16 through a series of experiments.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibitory effects of mir-15b-5p have been revealed in neuroblastoma, and it can restrain tumor progression by directly targeting MYcn proto-oncogene, bHlH transcription factor (18). luo et al (42) demonstrated that mir-15b-5p reduced proliferation, but induced apoptosis and cytotoxic activities of Pc12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…as a mature mirna, mir-15b-5p is spliced from the 5'-end of pre-mir-15b, which is a member of mir-16 family (15,16). Moreover, mir-15b-5p is upregulated in gastric cancer (15), liver cancer (17) and hepatocellular carcinoma (18)(19)(20)(21)(22), while it is lowly expressed in neuroblastoma (18) and prostate cancer (23). However, the biological functions and underlying mechanisms of mir-15b-5p in THca are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%